Indigent Consumers’ Protection at the Financial Services Market - Ćwieląg, Krzysztof; Maciejasz-Świątkiewicz, Marta (Journal of Finance and Financial Law, 2016)
The aim of the study is an answer to the question whether the protection of indigent consumers at the financial services market should be implemented differently in relation to the general rules and what elements should include this protection? Moreover – which entities should provide this protection – those that already exist at the market, or any other? The problem of protecting indigent people stems from the fact that in large part they are excluded from the mainstream market, which is subject of legal protection. Some people use the alternative market offer, or even the informal one. It seems, therefore, that the additional protection of indigent people should be targeted to these areas of the financial services market.